2009
DOI: 10.1038/hr.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-NAME-induced hypertension on melatonin receptors and melatonin levels in the pineal gland and the peripheral organs of rats

Abstract: Melatonin plays a role in blood pressure (BP) control. The aim of this study was to determine whether melatonin concentrations and melatonin receptor levels are altered in L-NAME-treated, NO-deficient hypertensive rats. Two groups of male adult Wistar rats were investigated: rats (n¼36) treated with NO-synthase inhibitor L-NAME (40 mg kg À1 ) and age-matched controls (n¼36). BP was measured weekly by tail-cuff plethysmography. After 4 weeks, L-NAME administration increased BP (178±1 vs. control 118 ± 1 mm Hg).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Expression of MT 1 was additionally confirmed at the protein level by Western blotting. These results extend our previous findings in the rat aorta (Benova et al 2009) and are in line with the MT 1 presence in other blood vessels in rats (Dubocovich and Markowska 2005) and the human aorta (Ekmekcioglu et al 2001). We confirmed the presence of MT 1 mRNA by two different RT-PCR techniques applying two different sets of primers and identified the amplicon by sequencing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Expression of MT 1 was additionally confirmed at the protein level by Western blotting. These results extend our previous findings in the rat aorta (Benova et al 2009) and are in line with the MT 1 presence in other blood vessels in rats (Dubocovich and Markowska 2005) and the human aorta (Ekmekcioglu et al 2001). We confirmed the presence of MT 1 mRNA by two different RT-PCR techniques applying two different sets of primers and identified the amplicon by sequencing.…”
Section: Discussionsupporting
confidence: 93%
“…While the expression of MT 1 protein had been shown (Benova et al 2009), demonstration of mRNA expression failed (Chucharoen et al 2003), and 125 I-MEL binding was not observed (Viswanathan et al 1990). Finally, while MT 2 mRNA expression was shown in human aorta (Ekmekcioglu et al 2003), a study in the rat aorta failed to detect the same (Chucharoen et al 2003).…”
Section: Introductionmentioning
confidence: 92%
“…MT1 expression was observed in the rat aorta [42,43,44], while these receptors were surprisingly localized mainly in the tunica adventitia and not in the smooth muscle and/or endothelial cells [43], and in rat caudal artery [45]. MT2 were observed in porcine coronary arteries [46], in rat caudal artery [45], but not in the aorta [43].…”
Section: Receptor-dependent Effects Of Melatonin On Blood Pressurementioning
confidence: 99%
“…However, in the same experiment, in peripheral organs, melatonin levels were not substantially changed. It has been suggested that increased melatonin production was insufficient to counterbalance the augmented melatonin consumption in the peripheral tissues [42]. Similarly, in rats with chronic immobilization stress and increased sympathetic nerve activity and enhanced circulating norepinephrine levels, the nocturnal melatonin levels were increased [127].…”
Section: Questions and Perspectivesmentioning
confidence: 99%
“…The data from our laboratory indicate that the melatonin level in the pineal gland was increased in L‐NAME‐hypertensive animals relative to these in control rats. It was suggested that the increased sympathetic tone or reduced NO production in the PVN in L‐NAME‐treated rats might have underlined the potentially compensatory enhancement of melatonin formation . Also, chronic immobilization stress in rats induced an enhancement of circulating norepinephrine levels along with the increase in nocturnal level of melatonin .…”
Section: Melatonin As a Potential Means Of Hr Reduction In Hypertensionmentioning
confidence: 99%